The use of spatial data for segmentation of the postal service market - Marković, Dejan; Grgurović, Biljana; Štrbac, Slavica (Technological and Economic Development of Economy, 2011)
Modern trends in the field of postal traffic imply the existence of a large number of providers who distribute these services. A trend of this kind sets highly rigorous requirements regarding structure and quality of the services. On the other hand, the users are a heterogenous group with specific characteristics, which significantly complicates the process of segmentation, choice of a target market and formulating of an adequate marketing strategy. Application of some standard methods of demographic and psychographic segmentation, in the opinion of the authors of this paper, results in very general grouping most often based on assumptions. The aim is to point out the significance of spatial data and how the results obtained by application of a geographic information system (GIS) can be used in the case of segmentation of the postal service market.